Language Acculturation: A Case Study of Madurese Community in Manduro, Jombang, East Java - sofa, sofa; saroh, yam (D3 English Program Universitas Merdeka Malang, 2017)
This article presents a case study of language acculturation particularly code-switching which emerges in Madurist community in Menduro, Jombang, East Java. The purpose of conducting this study was to portray the phenomenon of switching more than two languages and factors influencing it within the community to show the variety of Indonesian unique culture. To gain the data, interview was carried out and the recording script was elaborated. Based on the result, it was found that Madurist code-switch the languages of their mother tongue (Madurese), region based (Javanese) and national language (Bahasa Indonesia). The factors were marriage and trade.